2016
DOI: 10.1186/s12877-016-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

An intervention targeting fundamental values among caregivers at residential facilities: effects of a cluster-randomized controlled trial on residents’ self-reported empowerment, person-centered climate and life satisfaction

Abstract: BackgroundIn Sweden the national fundamental values for care of older people state that care should ensure that they can live in dignity and with a sense of well-being. Our hypothesis was that a caregiver intervention targeting the national fundamental values would improve perceived empowerment, person-centered climate and life satisfaction among older people living in residential facilities.MethodsThe study was a cluster-randomized controlled trial with a pre- and one post-test design, conducted in 27 units (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Persons with palliative care needs have also reported feeling appreciative about their accomplishments and about important people in their life (Hall et al, 2012), supporting the idea that gratitude could be an important outcome for them. Furthermore, empowerment has been defined as “a process of promoting and enhancing people's ability to meet their own needs and to mobilize the resources necessary to feel control over their lives” (Roos et al, 2016, p. 2). It has been described that a sense of control contributes to enhancing a person's dignity (Guo and Jacelon, 2014), and perceived loss of control is a risk factor for losing dignity (Monforte et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Persons with palliative care needs have also reported feeling appreciative about their accomplishments and about important people in their life (Hall et al, 2012), supporting the idea that gratitude could be an important outcome for them. Furthermore, empowerment has been defined as “a process of promoting and enhancing people's ability to meet their own needs and to mobilize the resources necessary to feel control over their lives” (Roos et al, 2016, p. 2). It has been described that a sense of control contributes to enhancing a person's dignity (Guo and Jacelon, 2014), and perceived loss of control is a risk factor for losing dignity (Monforte et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important that the staff members’ focus is not just on getting the work done2 but also on gaining the older patient’s trust. Ethical, caring actions should be carried out based on a need to accomplish the primary task and to provide good health care 17. The participation of older patients can be supported by the staff, whose individual perspectives can be called upon to create secure relationships 18.…”
Section: Introductionmentioning
confidence: 99%
“…Since older adults have their own unique criteria for a good life, a global judgment of life satisfaction may be useful to assess residents' psychological outcomes by allowing individuals to prioritize domains of their lives based on their own values, goals, and concerns. A recent national-level, cluster-randomized controlled trial in Sweden identified that new national fundamental values for the care of older adults had a significant effect on life satisfaction (Roos et al, 2016). These values focus on ensuring that residents are treated with dignity and with a sense of wellbeing in long-term care facilities, which is very similar to the core components of person-centered care.…”
Section: Introductionmentioning
confidence: 99%